Stability of supported Pd-based ethanol oxidation reaction electrocatalysts in alkaline media - Gentil, Tuani C.; Minichova, Maria; Briega-Martos, Valentín; Pinheiro, Victor S.; Souza, Felipe M.; Paulo C. Moura, João; César M. Silva, Júlio; Batista, Bruno L.; Santos, Mauro C.; Cherevko, Serhiy (Journal of Catalysis, 2024)
This study evaluates the dissolution of the supported electrocatalysts Pd/C, PdSn/C, PdNb/C, and PdFe3O4/C during ethanol oxidation reaction for Alkaline Direct Liquid Fuel Cells (ADLFC) applications. A scanning flow cell (SFC) combined to an inductively coupled plasma mass spectrometry (online ICP-MS) is used to assess the dissolution stability in a broad potential window. Accelerated stress tests with and without ethanol are developed using a rotating disk electrode (RDE) with dissolution products analysis by ex-situ ICP-MS. Potential profiles simulating those experienced by the catalyst during regular fuel cell operation were used. Sn and Fe catalysts demonstrate improved activity and stability compared with the material with Pd alone. For these reasons, PdSn/C and PdFe3O4/C are suitable for ADLFC applications. Severe Nb dissolution destabilizes Pd, increasing its leaching. This work demonstrates that while additional metals and oxides can improve the alcohol oxidation kinetics of Pd, these additives’ dissolution stability must already be considered at the catalyst design stage.
CRIS-Team Scopus Importer:2024-11-01
Keywords: Durability; Electrocatalysis; Ethanol oxidation reaction; Fuel cells; Palladium